PENGARUH KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU SMK SWASTA KRISTEN BNKP DARO-DARO LAHUSA BALAEKHA - Gulo, Denisman (Curve Elasticity: Jurnal Pendidikan Ekonomi, 2024)
Teacher development efforts are heavily influenced by school principals. If school principals can exercise supervision and control and coordinate educational resources, teachers' performance levels will improve. The purpose of this study is to determine the impact of the principal's leadership on the performance of BNKP Darodaro Baraekha Christian Private Vocational School. This type of research is descriptive and based on a quantitative approach. The research instrument was a questionnaire and the population and research sample consisted of her 38 teachers of BNKP Daro-daro Balaekha Christian Pocational School. Research shows that principal leadership influences teacher performance. Conclusion: As a leader, the principal is tasked with mobilizing all available resources within the school. The good performance of teachers in schools mainly depends on the ability of school principals to influence the behavior of teachers in carrying out their duties. Recommendations 1) School principals should strengthen their role as leaders in school educational institutions and improve the quality of their leadership, including providing continuous motivation to teachers. This motivation can be achieved by implementing a reward system for teachers who perform well. This helps improve teacher performance. 2) Teachers should increase their responsibility in carrying out their duties, follow the rules set by the principal as a leader, constantly discuss learning with the principal, and receive opinions and constructive criticism from the principal. We need to emulate the attitude. Always follow the principal's instructions for the student's progress.